Constructing regulable supports via non-stoichiometric engineering to stabilize ruthenium nanoparticles for enhanced pH-universal water splitting - Sheng Zhao; Sung-Fu Hung; Liming Deng; Wen-Jing Zeng; Tian Xiao; Shaoxiong Li; Chun-Han Kuo; Han-Yi Chen; Feng Hu; Shengjie Peng (Nature Communications, 2024)
Abstract Establishing appropriate metal-support interactions is imperative for acquiring efficient and corrosion-resistant catalysts for water splitting. Herein, the interaction mechanism between Ru nanoparticles and a series of titanium oxides, including TiO, Ti4O7 and TiO2, designed via facile non-stoichiometric engineering is systematically studied. Ti4O7, with the unique band structure, high conductivity and chemical stability, endows with ingenious metal-support interaction through interfacial Ti–O–Ru units, which stabilizes Ru species during OER and triggers hydrogen spillover to accelerate HER kinetics. As expected, Ru/Ti4O7 displays ultralow overpotentials of 8 mV and 150 mV for HER and OER with a long operation of 500 h at 10 mA cm−2 in acidic media, which is expanded in pH-universal environments. Benefitting from the excellent bifunctional performance, the proton exchange membrane and anion exchange membrane electrolyzer assembled with Ru/Ti4O7 achieves superior performance and robust operation. The work paves the way for efficient energy conversion devices.